2002
DOI: 10.1007/s102860200024
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cold face test bradycardia by means of spectral analysis

Abstract: The cold face test (CFT) is a non-invasive challenge maneuver of the autonomic nervous system which activates the peripheral sympathetic and the cardiac parasympathetic nervous system and induces peripheral vasoconstriction and bradycardia. The physiology of CFT-induced bradycardia is still controversial. The heart rate decrease might result from a direct central up-regulation of cardiovagal activity or might be a secondary effect of baroreceptor activation or of changes of respiration. The purpose of this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
36
2
9

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 33 publications
(71 reference statements)
2
36
2
9
Order By: Relevance
“…It is well established that face cooling elicits a pressor response in humans for up to 180 s (1,3,7,11,14,15,18,19,21,22). Data from the present study extend these findings and show that face cooling-induced increases in blood pressure can be sustained for at least 15 min (Fig.…”
Section: Face Cooling Elicits Sustained Increases In Blood Pressuresupporting
confidence: 87%
See 3 more Smart Citations
“…It is well established that face cooling elicits a pressor response in humans for up to 180 s (1,3,7,11,14,15,18,19,21,22). Data from the present study extend these findings and show that face cooling-induced increases in blood pressure can be sustained for at least 15 min (Fig.…”
Section: Face Cooling Elicits Sustained Increases In Blood Pressuresupporting
confidence: 87%
“…Cooling of the forehead and cheeks evokes a similar, yet less pronounced, response in humans (1,3,7,11,14,15,18,19,21,22), which occurs secondary to stimulation of the cold afferents of the trigeminal nerve (10,17). Face cooling in humans simultaneously stimulates the parasympathetic and sympathetic nervous systems, evoking bradycardia and peripheral vasoconstriction (1,3,7,11,14,15,18,19,21,22). In humans, reductions in heart rate are not sufficient to reduce cardiac output (3).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[1] Human studies have shown vagal attenuation in response to immersion of face and hand in ice water. [2][3][4] Literatures have investigated whether water drinking in normal subjects affected peripheral sympathetic neural discharge and its effect on vascular resistance. The last two decades have witnessed the recognition of a significant relationship between the autonomic nervous system and cardiovascular mortality, including sudden cardiac death.…”
Section: Introductionmentioning
confidence: 99%